ON PERFECTION OF CONSTRUCTIVE AND TECHNOLOGICAL FORMS OF PLATE AND RIBBED TRANSFER STRUCTURES FROM GLUED TIMBER - V. A. Utkin; P. N. Kobzev (Вестник СибАДИ)
Introduction. The paper presents the prefabricated whole-glued slab-ribbed superstructures, containing glued beams (fins) and a multi-layered wood-panel from horizontal cross-layers of blank boards, laid successively on glued beams and each other and interconnected by glue seams.Materials and methods. Because of the development of the constructive and technological forms of the considered superstructures, the authors propose the structure composed of plate and ribbed integrally transported prefabricated sections with the width of 3-3.5 m. The authors highlight that the combined action of the detached sections is provided through the nodes of combination on the adjacent ribs of  the sections without the complicated compression of all the elements of the superstructure including beams, plates, and diaphragms.Results. The analysis of the stress-deformed span by two methods indicates that both methods determine, with a sufficient degree of accuracy, the nature of the distribution of stresses and strains in sections of the structure. Moreover, the obtained values of the maximum deflections and stresses do not exceed the limit values established by the norms and the corresponding values in a similar construction of the structure with a solid timber slab.Conclusions. The paper shows that the proposed construction with the division of the whole-glued multiridged span structure into separate prefabricated, factory-made sections would significantly expand the usage of laminated wood in bridge construction.